(untitled) (Research, Society and Development, 2022)
The poultry litter comes from avian production, which if not treated properly can negatively impact the environment. The objective was to obtain a substrate with composted poultry litter to offer an alternative to the production and growth of Eucalyptus camaldulensis. This material was composted and characterized in terms of macronutrient content, being used in two experimental trials: seed germination and initial growth of Eucalyptus camaldulensis seedlings. The seeds were planted and filled with commercial substrate and different percentages of composted poultry litter, whose control treatment was the substrate based on pine bark and vermiculite. 100% and 200% of the recommended nitrogen dose for the crop were supplied, with the control treatment being pots filled with cerrado soil and mineral fertilization in order to provide 25g of N/plant. For the initial growth experiment, the Completely Randomized Design (DIC) was used with treatments distributed in a 4x2x17 factorial scheme (4 treatments, 2 nitrogen doses and time). These showed higher nitrogen contents the greater the number of lots of birds housed on the same litter. The seeds had late germination for the treatments with poultry litter in the proportions of 20% and 50% and the seedlings did not survive. In treatments with 100% with poultry litter there was no germination. The best treatment was the composted poultry litter with the highest number of reuses and with 100% of the nitrogen dose. All seedlings showed good IQD indexes indicating chance of survival in the field.